Development of an Open-Source Sensing System for the Measurement of Dissolved CO2 Throughout a Microalgal Photobioreactor ... - Johnson, Alexander James (Newcastle University, 2024)
In order to optimise growing conditions for microalgae, it is important to be able to determine the concentration of dissolved CO 2 within the algal media. Typically, pH measurements are taken in order to indirectly determine the dissolved CO 2 concentration, as some CO 2 reacts with H 2 O to produce carbonic acid (H 2 CO). However, this is an unreliable method since the alkalinity of the media will determine its buffering capacity and therefore its ability to resist changes in pH. This means that without knowledge of the alkalinity of the solution, dissolved CO 2 concentration cannot be determined from pH alone. Additionally, the presence of additional acidic or basic chemicals in the media will impact the pH and therefore impact the calculated dissolved CO 2 concentration, especially problematic in scenarios such as wastewater treatment where chemicals such as ammonia are present. As a result, a more direct measurement is preferable through membrane diffusion of CO 2 . This is where a gas-permeable, ...